THE EFFORTS OF AN ISLAMIC EDUCATION TEACHER IN INTEGRATING RELIGIOUS MODERATION VALUES THROUGH THE HASTHALAKU CULTURE AT SMAN 1 KARTASURA, SUKOHARJO, CENTRAL JAVA - Alfiyah Intan Nur; Yayan Andrian, S.Ag., M.ED.MGMT.; Kholis Firmansyah, S.H.I., M.S.I. (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This study was driven by the fact that cases of intolerance are still found in Indonesia, including within educational institutions. These conditions show the need for better understanding and application of religious moderation values. One of the efforts to provide students with an understanding of religious moderation values is through the efforts of Islamic education teachers in integrating these values through the Hasthalaku culture, so that students are able to understand and apply the teachings of Islam based moderation values while also respecting local culture as a form of moderation attitude. Hasthalaku Solo, which is part of Javanese culture, is in line with religious moderation values, as both aim to create a harmonious and tolerant life. This study aims to explore the efforts of Islamic education teacher in integrating religious moderation values through the Hasthalaku culture at SMAN 1 Kartasura, Sukoharjo Central Java. This study uses a descriptive qualitative approach. The research was conducted from October 2024 to March 2025. The subjects of the study were the Islamic education teacher of class XI F9 and the Muslim students of class XI F9. Data were collected through observation, interviews, and documentation. The validity of the data was ensured using source and method triangulation. The data were analyzed through the stages of data condensation, data display, and conclusion drawing. The results of this study show that the Islamic education teacher integrates religious moderation values both inside and outside the teaching and learning process by using Hasthalaku values to strenghthen students’ understanding of the importance of living in peace, respecting differences, appreciating culture, loving the homeland, and practicing justice. This integration is carries out by embedding these values into Islamic education lessons, using learning strategies such as discussion and case studies, as well as through the teacher’s personal example.